Differentiation of Species and Provenance of Palm-Leaf Manuscripts Using Fourier Transform Infrared Spectroscopy and Chemometrics - Lucas F. Voges; Nils Horn; Giovanni Ciotti; Stephan Seifert (Chemosensors)
For authentication and interpretation of palm-leaf manuscripts, material analyses are required that enable identification of specific characteristics of written artefacts. In this study, we apply infrared spectroscopy (DRIFTS) in combination with principal component analysis (PCA) as a fingerprinting technique for the analysis of eleven palm-leaf manuscripts. We demonstrate that manuscript-specific information is obtained and that a differentiation regarding the taxonomic species of palm leaves used for production and of their geographical origin in South and Southeast Asia is possible. The results show the potential of infrared spectroscopy for fingerprinting and authentication of written artefacts.